2021
DOI: 10.1021/jacs.1c01580
|View full text |Cite
|
Sign up to set email alerts
|

High-Entropy van der Waals Materials Formed from Mixed Metal Dichalcogenides, Halides, and Phosphorus Trisulfides

Abstract: The charge, spin, and composition degrees of freedom in a high-entropy alloy endow it with tunable valence and spin states, infinite combinations, and excellent mechanical performance. Meanwhile, the stacking, interlayer, and angle degrees of freedom in a van der Waals material bring to it exceptional features and technological applications. Integration of these two distinct material categories while keeping their merits would be tempting. On the basis of this heuristic thinking, we design and explore a new ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 44 publications
(59 reference statements)
0
66
0
Order By: Relevance
“…Cubic A6B12C8 Td AuTe2Se4/3 [29,30] Figure 2. Crystal growth and element distribution of HEX materials [17,19] .…”
Section: General Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Cubic A6B12C8 Td AuTe2Se4/3 [29,30] Figure 2. Crystal growth and element distribution of HEX materials [17,19] .…”
Section: General Featuresmentioning
confidence: 99%
“…Figure 4. The intercalation of HEX [17] . (a) X-ray diffraction patterns of polycrystalline (black), single-crystalline (orange), and potassium-intercalated (blue) (TiVCrNbTa)S2.…”
Section: Exfoliation and Intercalationmentioning
confidence: 99%
“…Hosono et al developed a mechanical exfoliation method to synthesize a series of high-entropy van der Waals 2D materials (dichalcogenides, halides, and phosphorus trisulfides) with an intriguing set of properties. 46 Wang et al developed high-entropy layered double hydroxides (HE-LDH) (FeAlCrCoNiZnCu)–OH intercalated with CO 3 2− by a hydrothermal method and exfoliated them to ultrathin defective nanosheets with a diameter of 50 nm with argon plasma. 42 Wang et al also reported the synthesis of spinel-type high-entropy oxide (FeCrCoNiCu) 3 O 4 nanosheets with diameters up to 100 nm by oxygen plasma exfoliation of HE-LDH.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggest that the HEA states would affect the superconducting gap opening. More recently, HEA-type van-der-Waals layered superconductors were designed and synthesized [ 11 ]. For the cases of three-dimensional structures, we have investigated the effect of the introduction of HEA sites in NaCl-type M Te [ 12 , 13 , 14 ] and A15-type Nb 3 X and V 3 X [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%